Politeness of Filipino HEI Students in Realizing Computer-Mediated Requests - dela Cruz-Rudio, Lourdes (International Journal of Language and Literary Studies, 2025)
Pragmatic competence is an essential ingredient in the success of human interaction; it ensures that a message is expressed and understood appropriately based on the norms of a given discourse community. This study was conducted to offer an analysis of the realization of the speech act of request among higher education students sent via email to their professor in the light of the Politeness construct. Forty-eight emails of requests sent to the researcher were analyzed using the frameworks of Blum-Kulka and Olshtain (1983) and Brown and Levinson (1978). Through discourse analysis, this qualitative study presents prominent strategies used by the students in their request head acts and accompanying statements that also indicate politeness. It is concluded that the students exhibit pragmatic competence with their use of appropriate request and politeness strategies to serve their communicative purposes. However, their use of some pragmatic markers might be indicative of either politeness or negative pragmatic transfer or both. Finally, the study offers recommendations for future researchers as well as pedagogical implications.